Effect of the level of alveolar atrophy on implant placement accuracy in guided surgery for full-arch restorations supported by four implants: an in vitro study - BAYRAM, FERİT (My University, 2023)
Background A fxed screw-retained full-arch restoration supported by four implants is a popular treatment option for edentulous arches. Optimal alignment of implants is quite challenging in extremely atrophied edentulous cases, and a small amount of deviation is expected during guided surgery. This study aimed to compare implant accuracy among edentulous jaws with various levels of atrophy. Methods Five separate copies of each Cawood and Howell model (III–V) were produced for the maxilla and mandible. A total of 120 implants (30 models). The implant accuracy was assessed based on angular deviations at the base (angle, 3D ofset, distal, vestibular, and apical) and tip (3D ofset, distal, vestibular, and apical). Results The atrophy level of the jaws had a statistically signifcant efect on deviation; implants showed greater deviation from the planned location as the atrophy level increased. Conclusion Given that implant deviation increased with the degree of atrophy, a greater safety margin from important anatomical structures is recommended when planning implant location for guided surgery in Cawood and Howell V cases.
Keywords: Dental implant; Computer-aided designs; CAD-CAM; Edentulous jaw; Bone screws; Atrophy